P244 HSV serotypes in first episode genital herpes in North West Northern Ireland. (30th June 2016) - Melaugh, Lynsey; Perry, Melissa
Abstract : Background/introduction: Most populations have observed an increase in the role of HSV-1 as a cause of genital herpes simplex virus (HSV) Aims: To analyse HSV serotypes in first episode genital herpes in North West Northern Ireland. Methods: All patients who tested positive for HSV and were coded as C10A from 01/03/2015 – 01/03/2016 were included. Demographic details including sex, age, ethnicity and sexual identity were recorded. The confirmed serotype (HSV-1 vs HSV-2) was noted. Results: A total of 36 cases of first episode genital HSV was seen. 100% were white Caucasian (35/36 White UK); 29 were female and 7 were male. All females self-reported as heterosexual and of the 2/7 men were MSM. Overall median age at diagnosis was 23 years old (range 16–40). Of the 36 positive PCR tests 83.3% (30) were HSV-1 and 6.7% (6) were HSV-2. The median age at diagnosis for HSV-1 was also 23 years (range 16–32); 26 were female and 4 male. Of the 6 positive who tested positive for HSV-2, 3 each were male and female. Conclusion: It is well documented that HSV-1 is increasingly prevalent as a cause of first episode genital HSV, our rate of 83% for HSV-1 infection is notably high. Although not a significant diagnostic or management challenge this may reflect a lower prevalence of HSV-2 infection within the local sexually-active population or an increasing level of sexual risk behaviour capable of transmitting HSV-1 infection. Local clinicians need to be aware of the differences in prognosis for HSV-1 infection such that accurate information and advice can be given to help reduce stigma traditionally attached to HSV-2 infection.